2011
DOI: 10.3168/jds.2011-4258
|View full text |Cite
|
Sign up to set email alerts
|

A multi-level hierarchic Markov process with Bayesian updating for herd optimization and simulation in dairy cattle

Abstract: Herd optimization models that determine economically optimal insemination and replacement decisions are valuable research tools to study various aspects of farming systems. The aim of this study was to develop a herd optimization and simulation model for dairy cattle. The model determines economically optimal insemination and replacement decisions for individual cows and simulates whole-herd results that follow from optimal decisions. The optimization problem was formulated as a multi-level hierarchic Markov p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 66 publications
2
21
0
Order By: Relevance
“…These culling rules may therefore provide more realistic results than the assumption of optimal culling decisions used in other models (e.g. Demeter, et al, 2011) because in practice culling decisions are not always economically optimal.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…These culling rules may therefore provide more realistic results than the assumption of optimal culling decisions used in other models (e.g. Demeter, et al, 2011) because in practice culling decisions are not always economically optimal.…”
Section: Figurementioning
confidence: 99%
“…However, as increased estrus detection rates cause shorter calving intervals, the random culling process will lead to an increase in the annual number of culled cows for the situation with the activity meter. Culling is often not a random process, fertility problems in general, and more specifically failure to conceive, are known reasons for culling (Brickell and Wathes, 2011, Dechow and Goodling, 2008, Demeter, et al, 2011. Some studies have suggested that approximately 20% of the cows were culled because of fertility problems (Brickell andWathes, 2011, Dechow andGoodling, 2008).…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations